N-Alkanes and stable C, N isotopic compositions as identifiers of organic matter sources in Posidonia oceanica meadows of Alexandroupolis Gulf, NE Greece. Issue 1 (15th October 2015) - Apostolopoulou, Maria-Venetia; Monteyne, Els; Krikonis, Konstantinos; Pavlopoulos, Kosmas; Roose, Patrick; Dehairs, Frank
Highlights: We measured n -alkanes and isotopic composition in various samples in the Aegean Sea. Terrestrial and petroleum origin in Alexandroupolis Gulf was tested from 2007 to 2011. We provide baseline information on n _alkanes and isotopic composition for P. oceanica . Abstract: We analyzed n -alkane contents and their stable carbon isotope composition, as well as the carbon and nitrogen isotope composition (δ 13 C, δ 15 N) of sediment organic matter and different tissues of Posidonia oceanica seagrass sampled in Alexandroupolis Gulf (A.G.), north-eastern Greece, during 2007–2011. n -Alkane contents in P. oceanica and in sediments showed similar temporal trends, but relative to bulk organic carbon content, n -alkanes were much more enriched in sediments compared to seagrass tissue. Individual n -alkanes in sediments had similar values than seagrass roots and rhizomes and were more depleted in 13 C compared to seagrass leaves and sheaths, with δ 13 C values ranging from −35‰ to −28‰ and from −25‰ to −20‰, respectively. n -Alkane indexes such as the Carbon Preference Index, carbon number maximum, and n -alkane proxy 1 (C23  + C25 /C23  + C25  + C29  + C31 ) indicate strong inputs of terrestrial organic matter, while the presence of unresolved complex mixtures suggests potential oil pollution in some sampled areas.